2017
DOI: 10.21608/ejvs.2017.2040.1022
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Profile, Antioxidant Status and Some Biochemical Parameters during Pregnancy and Periparturient Period in Dromedary She Camel

Abstract: THIS STUDY aimed to determine the changes in the hormonal and biochemical profile of pregnant dromedary camels to provide a baseline data under Egyptian climatic conditions. Blood samples were collected from15 pregnant she-camels aged 8-11 years old just postconception and thereafter monthly during gestation period and during periparturient period (at days 15, 7,4and 1prepartum,at parturition and at days 1, 4, 7 and 15 postpartum).Progesterone level increased significantly (P<0.05) after conception and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In our study, cortisol was significantly (P<0.05) increased in the post-partum period than in other physiological statuses. These results agree with Ibrahim et al (2017) who reported a significant increase in serum cortisol level began from day 15 to day 1 pre-partum with a maximum level at the day of parturition. In addition, Agarwal et al, (1992) and Mohamed, (2006) demonstrated that cortisol concentrations were high at parturition and significantly decreased within the lactation period and attributed such increase to the increase of ACTH secretion from the fetal pituitary in the late pregnancy, which stimulates the rapid growth of the fetal adrenals, leading to a rise in the concentration of serum cortisol, which enters the maternal circulation and rise the maternal serum cortisol level.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, cortisol was significantly (P<0.05) increased in the post-partum period than in other physiological statuses. These results agree with Ibrahim et al (2017) who reported a significant increase in serum cortisol level began from day 15 to day 1 pre-partum with a maximum level at the day of parturition. In addition, Agarwal et al, (1992) and Mohamed, (2006) demonstrated that cortisol concentrations were high at parturition and significantly decreased within the lactation period and attributed such increase to the increase of ACTH secretion from the fetal pituitary in the late pregnancy, which stimulates the rapid growth of the fetal adrenals, leading to a rise in the concentration of serum cortisol, which enters the maternal circulation and rise the maternal serum cortisol level.…”
Section: Discussionsupporting
confidence: 93%
“…According to numerous studies, in camels, high cortisol blood concentrations are a reliable indicator of the state of physical, psychological and physiological stress (Saeb et al, 2010;El khasmi et al, 2015;Tharwat et al, 2015;Abd-El-Rahman et al, 2017;Ebissy et al, 2019). Compared to the reference values reported by Saeb et al (2010), the higher cortisol concentrations mentioned in the present study in camels having been exposed to the different pre-slaughter operations for a long time, prove that the latter are more stressful.…”
Section: Discussionsupporting
confidence: 46%
“…Blood biochemical parameters are the established indicators to provide information about the health status of pregnant animals for their successful transfer from gestation to lactation stage (57). Late pregnancy is characterized by severe metabolic changes and a rapid decrease in plasma protein level was also noticed in different other animal species during this period (58)(59)(60). The plasma protein level drops promptly in the last trimester due to high amino acid requirements for developing fetus and preparation of the mammary system for subsequent lactation stage (61).…”
Section: Discussionmentioning
confidence: 99%